Medicaid Expansion and 2-Year Survival in Women With Gynecologic Cancer: A Difference-in-Difference Analysis. Issue 12 (December 2022) - Huepenbecker, Sarah P.; Fu, Shuangshuang; Sun, Charlotte C.; Zhao, Hui; Primm, Kristin M.; Giordano, Sharon H.; Meyer, Larissa A.
Abstract : (Abstracted from Am J Obstet Gynecol 2022;227:482.e1–482.e15) In 2014, the Affordable Care Act gave the option for states to expand Medicaid to provide health care coverage to adults with incomes below 138% of the federal poverty level. This expansion was unequally adopted, and multiple studies have demonstrated expansion to be associated with improved insurance coverage, early-stage diagnosis, and timely treatment of women with gynecologic malignancies.